Characterization of the chemical constituents and in vivo metabolic profile of Scutellaria barbata D. Don by ultra high performance liquid chromatography with high‐resolution mass spectrometry. Issue 9 (6th March 2022) - Kang, An; Jiang, Jialu; Li, Qin; Sheng, Xianjie; Chen, Yan; Tan, Jiani; Li, Liu; Shen, Weixing; Tang, DongXin; Cheng, Haibo; Sun, Dongdong
Abstract: Scutellaria barbata D. Don ( S. barbata ) is one of the most frequently used anticancer herb medicine in China. Mechanistic understanding of the biological activities of S. barbata is hindered by limited knowledge regarding its components and metabolic profile. In this study, ultra‐high‐performance liquid chromatography coupled with high resolution mass spectrometry (quadrupole time‐of‐flight mass spectrometry) was used to identify the chemical constituents in S. barbata and their metabolic profiles in rats. By applying cleavage rules and comparison with reference substances, 89 components were identified in S. barbata, which included 45 flavonoids, 28 diterpenoids, 10 phenolics, and 6 others. A total of 110 compounds, including 32 prototype compounds and 78 metabolites, were identified or tentatively characterized in vivo. Methylation, sulfonation, and glucuronidation were the main metabolic pathways, which could be attributed to the fact that several of the compounds in S. barbata have phenolic hydroxyl groups. This is the first systematic study on the chemical constituents and in vivo metabolic profile of S. barbata . The analytical method features a quick and comprehensive dissection of the chemical composition and metabolic profile of S. barbata and provides a basis for exploring its various biological activities.